Studi Patologi Birokrasi Dalam Pelayanan Administrasi Kependudukan Di Kantor Kecamatan Jekan Raya Kota Palangka Raya - Nurhasanah, Nurhasanah; Yusnalia, Yusnalia (Pencerah Publik, 2019)
The purpose of this research is to know about bureaucratic pathology study in the Population administration services in Jekan Raya Sub-district office. The method used in this study is qualitative. The primary data in this research is the employee who provides service and community in Jekan Raya Sub-district office. Secondary Data of materials, including books, articles, scientific papers, newspapers, and scientific journals. Based on the research on the pathology of bureaucracy that appears in Jekan Raya district office seen from the complaints of some people in Jekan Raya subdistrict office still there is a convoluted service and existence of bureaucracy also still Very low. To be able to overcome bureaucracy pathology structured in Jekan Raya subdistrict, which must be done by Jekan Raya subdistrict, namely for low serving culture should perform quality public services, where the pattern of service implementation From the re-oriented government as a provider of service-oriented to the needs of the community as a user. Advice on the need for improvement of population administration services to improve the optimal service to the community, such as efforts to add facilities and infrastructure, should the government of Jekan Raya subdistrict can disseminate brochures on Service operational standard for the public to know the procedures of its treatment, the government of Jekan Raya subdistrict can provide information to the public to convey or provide a letter if there are complaints in the box/counter that has been Provided.